Homogeneously dispersed cobalt/iron electrocatalysts with oxygen vacancies and favorable hydrophilicity for efficient oxygen evolution reaction. (23rd March 2021) - Zhang, Zhengyuan; Xu, Yuqi; Wu, Meng; Luo, Bifu; Hao, Jinhui; Shi, Weidong
Abstract: Rational design of highly conductive and hydrophilic electrocatalysts are extremely important to promote their oxygen evolution reaction (OER). In this work, a homogeneously dispersed carbon-based cobalt/iron catalyst (Co/Fe–C) with abundant oxygen vacancies and favorable hydrophilicity is fabricated via a facile metal-polyphenol complexes strategy. The tannic acid (TA) and fulvic acid (FA) derived 0.3 Co/Fe–C catalysts show greatly similar morphologies, as well as the performance optimization process of electrocatalytic OER. Specifically, the TA-derived 0.3 Co/Fe–C catalyst exhibits an overpotential of 284 mV at 10 mA cm −2 for OER in alkaline electrolyte. Combined a series of characterization techniques suggest that abundant oxygen vacancies and favorable surface hydrophilicity can improve electronic conductivity of the catalyst and accelerate reactant adsorption and charge transfer rate on the catalyst surface, thus promoting OER activity of the catalysts. This study might provide a new perspective to construct advanced electrocatalysts with oxygen vacancies and hydrophilic surface for electrocatalytic applications. Graphical abstract: Image 1 Highlights: A facile metal-polyphenols complexes strategy for synthesizing Co/Fe–C catalysts. Oxygen vacancies and hydrophilicity result in highly activity of Co/Fe–C catalyst. 0.3 TA− Co/Fe–C catalyst revealed excellent OER activity of 284 mV at 10 mA cm −2 . This work realizes low-temperature synthesis of conductive and hydrophilic catalysts.